2017
DOI: 10.1016/j.joca.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 is not involved in synovial inflammation and cartilage destruction in collagenase-induced osteoarthritis

Abstract: IL-1α and IL-1β are not involved in synovial inflammation and cartilage destruction during CiOA, implicating that other mediators are responsible for the joint damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…In the current Special Issue, van Dalen and colleagues revisit IL-1 as a target in OA. Despite performing these studies in arguably a more inflammatory model of OA (collagenase induced), they show that IL-1α/β deletion confers no reduction in cartilage loss or synovial inflammation [12]. In fact, the data suggest a trend towards increased cartilage damage in the knockout animals compared with wild type, agreeing with increased disease reported by Clements et al .…”
supporting
confidence: 53%
“…In the current Special Issue, van Dalen and colleagues revisit IL-1 as a target in OA. Despite performing these studies in arguably a more inflammatory model of OA (collagenase induced), they show that IL-1α/β deletion confers no reduction in cartilage loss or synovial inflammation [12]. In fact, the data suggest a trend towards increased cartilage damage in the knockout animals compared with wild type, agreeing with increased disease reported by Clements et al .…”
supporting
confidence: 53%
“…We also reported here that IL-1α is not involved in cartilage damage and synovial inflammation as, in the MNX model, the phenotype of IL-1α −/− was similar to that of WT mice. In agreement with the lack of a protective role of IL-1 deficiency in experimental OA, in another model of experimental OA, the collagenase-induced model of OA, mice deficient for both IL-1α and IL-1β (IL-1αβ −/− ) developed cartilage destruction and synovial inflammation similar to WT mice (van Dalen et al, 2016). Interestingly, histological scoring of the cartilage lesion showed a trend toward increased damage in IL-1 deficient mice, although this increase did not reach significancy.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, histological scoring of the cartilage lesion showed a trend toward increased damage in IL-1 deficient mice, although this increase did not reach significancy. The lack of a pathogenic role of IL-1 has been further confirmed in the collagenase-induced model by the lack of effect of IL-1Ra treatment in WT osteoarthritic mice (van Dalen et al, 2016). We previously reported that intra-articular BCP crystals can elicit synovial inflammation and cartilage degradation suggesting that BCP crystals have a direct pathogenic role in OA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is an increase in the incidence rate of OA with the aging of population, thus it is necessary to find an effective strategy for the treatment of OA [2] .During the progression of OA, the increased expression of interleukin-1β (IL-1β) in the articular cartilage and synovium leads to the destruction of cartilage, downregulation of type II collagen [3] .Furthermore, IL-1β has the function of inducing the chondrocyte release of prostaglandin E2 (PGE2) and nitric oxide (NO). Thus, reducing the IL-1β in articular cavity could delay the development of OA [4] .Resveratrol is a common polyphenolic compound in the skin of red grapes [5] . Resveratrol exhibits anti-ageing, anti-inflammatory, and anti-oxidant activities, and has cardio-, neuro-, and chondroprotective effects as proved by many studies [6] .…”
mentioning
confidence: 99%